Gender-associated cardiometabolic risk profiles and health behaviors in patients with type 2 diabetes: a cross-sectional analysis of the Joint Asia Diabetes Evaluation (JADE) program - Lim, Lee Ling; Lau, Eric S H; Kong, Alice P S; Fu, Amy W C; Lau, Vanessa; Jia, Weiping; Sheu, Wayne H H; Sobrepena, Leorino; Yoon, K H; Tan, Alexander T B; Chia, Yook Chin *; Sosale, Aravind; et al. (Elsevier, 2023)
Background: In Asia, diabetes-associated death due to cardiorenal diseases were 2-3 times higher in women than men which might be due to gender disparity in quality of care and health habits.